2007
DOI: 10.1159/000109612
|View full text |Cite
|
Sign up to set email alerts
|

The molecular basis of the folate-sensitive fragile site FRA11A at 11q13

Abstract: We report on the molecular basis of the rare, folate-sensitive fragile site FRA11A in chromosome band 11q13 in a family with cytogenetic expression. Five individuals express the fragile site and one was mentally retarded. Expansion of a polymorphic CGG-repeat located at the 5′ end of the C11orf80 gene causes FRA11A. The CGG-repeat elongation coincides with hypermethylation of the adjacent CpG island and subsequent transcriptional silencing of the C11orf80 gene. This gene has no homology with known genes. A rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…D). This is consistent with the local transcriptional repression associated with FRAXA [Oberle et al., ] and other reported FSFS [Debacker et al., ; Winnepenninckx et al., ; Metsu et al., ].…”
supporting
confidence: 91%
“…D). This is consistent with the local transcriptional repression associated with FRAXA [Oberle et al., ] and other reported FSFS [Debacker et al., ; Winnepenninckx et al., ; Metsu et al., ].…”
supporting
confidence: 91%
“…Therefore, our results indicate that the deletion sequences identified here most likely represent a common fragile site. This is further strengthened by the report that the rare fragile site FRA11A is caused by expansion of a CCG repeat in the 5' end of the C11orf80 gene, located 660kb telomeric from D11S913 [39]. Further, loss of heterozygosity studies has identified a number of tumor suppressor genes at chromosome 11q13.1 [4043].…”
Section: Discussionmentioning
confidence: 99%
“…FRAXA is a rare, folate sensitive fragile site (FSFS) associated with a trinucleotide repeat (CGG) expansion mutation in the 5′ UTR of the FMR1 gene resulting in fragile X syndrome, the most common inherited intellectual disability syndrome [20]. Twenty-six other FSFS have been reported cytogenetically but only eight of these have been molecularly characterized: FRAXA [20], FRAXE [21], FRAXF [22], FRA16A [23], FRA11B [24], FRA10A [25], FRA12A [26] and FRA11A [27]. To date, all characterized FSFS are due to a CCG/CGG trinucleotide repeat expansion.…”
Section: Introductionmentioning
confidence: 99%